Dinamika Pesantren Modern dan Salafi dalam Perspektif Kebijakan Pendidikan Islam - Putra, Wahyudi; Sujirman, Sujirman; Riyan, Riyan; Asha, Lukman; Warlizasusi, Jumira; Fakhruddin, Fakhruddin (An-Nahdloh: Journal of Education and Islamic Studies, 2025)
Pesantren are the oldest Islamic educational institutions in Indonesia, broadly categorized into two main models: salafi and modern pesantren. Each features distinct curriculum systems, educational philosophies, and responses to national education policies. This study aims to compare the dynamics of these two pesantren models within the framework of Islamic education policy in Indonesia. Employing a descriptive-qualitative approach through literature and policy analysis, this article critically examines their similarities and differences. The findings indicate that salafi pesantren excel in preserving classical Islamic scholarship and instilling strong religious values, yet are less responsive to the demands of the national education system. In contrast, modern pesantren are more adaptive to the national curriculum and contemporary needs, though they risk losing their traditional pesantren identity. Both face challenges in systemically integrating with existing national education policies. Therefore, this article recommends the development of a more integrative and contextual Islamic education policy model that accommodates the unique characteristics of both pesantren types within the national education framework. The study contributes to shaping a more inclusive, equitable, and sustainable reform of Islamic education in Indonesia. Keywords: salafi pesantren, modern pesantren, Islamic education policy